The Development of Mismatch Responses to Mandarin Lexical Tone in 12- to 24-Month-Old Infants - Cheng, Ying-Ying; Lee, Chia-Ying (Frontiers in Psychology, 2018)
This study explores the development of mismatch responses (MMRs) to Mandarin lexical tone changes in infants at 12, 18, and 24 months of age using the multi-deviant oddball paradigm with the low dipping Tone 3 (T3) as the standard, the high level Tone 1 (T1) as the large, and the high rising Tone 2 (T2) as the small deviant. The results show that the large acoustic change between T1/T3 elicited mismatch negativity (MMN) in all three age groups. The small acoustic change between T2/T3 elicited a positive mismatch response (P-MMR) at 12 and 18 months of age, but no MMR was found to the T2/T3 change at 24 months. The coexistence of MMN and P-MMR in the same age group implies that different mechanisms were used for discriminating large and small deviants. Infants were able to detect the T1/T3 change automatically and showed adult-like MMN as early as 6 months of age. However, the detection of the T2/T3 change remains effortful in infants under 24 months of age. These findings support the notion that MMN and P-MMR may be used to index the maturation of speech perception.